Tinjauan Pelaksanaan Konsinyasi Sebagai Tindakan Hukum Pemerintah Menurut Prinsip Welfare State - Renard Kananda Dipta; Erik Syaputra Johan (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2022)
Indonesia as a constitutional state is clearly guided by the existing rules in policies relating to the rights of its citizens. One aspect of the policy that is directly related to residents is land acquisition. Procurement of public welfare land is one of the special functions of the government to carry out administrative tasks. The Public Interest states that the government transfers ownership rights to land by giving compensation to the previous owner in a fair manner. If there is a refusal from the owner of the land rights, the legal instrument regulates the existence of a consignment mechanism to provide compensation through the courts. However, the consignment mechanism is carried out without considering the principles of justice and humanity and does not use proper judgment. Thus it is contrary to the principle of the welfare state which holds that the actions taken by the government are for the welfare of the people. This study aims to find out the regulations for implementing consignments in Indonesia and reviewing the implementation of consignment actions by the government according to the welfare state principle. This study uses a normative method by studying the mechanism of land acquisition in the public interest. This study uses primary, secondary, and tertiary legal sources. The results of the study are that consignment can be interpreted as a legal action by the government in the private sphere and in accordance with the principles of the rule of law and the concept of a welfare state, provided that the government cannot ignore the principles of justice and humanity.